The Evidence Synthesis Institute: Building a High Impact Training Program and Supportive Community for an Emergent Area of Librarianship - Kocher, Megan; Riegelman, Amy; Kibbee, Matthew; Bostrom, Molly; Marsalis, Scott; Young, Sarah; Premji, Zahra; Bahureksa, Lindsay; Bishop, Natasha; Chimwaza, Gracian; Comer, Cozette; DiGiovine, Elizabeth (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2026)
Objective – Seeing an absence of training opportunities for librarians supporting evidence synthesis outside of the health sciences, a collaborative team of librarians sought grant funding, developed a curriculum, and facilitated community building to provide this training.Methods – The present case study describes the identification of a training gap, multi-faceted efforts made to fill that gap, and evaluation via pretests and post-tests to continuously improve the program.Results – The Evidence Synthesis Institute (ESI) was launched in 2020. An application process is used to select the 50-person ESI cohort, with an average acceptance rate of 37%. To date, over 500 individuals have attended the Evidence Synthesis Institutes. Pre- and post-institute surveys show consistent gains in confidence to perform a variety of evidence synthesis skills. Additionally, we developed a self-paced online course which has over 750 enrolled learners with 118 having completed at least 90% of the course.Conclusion – This case study provides a model for designing, implementing, and assessing a training program and community of practice for an emergent skillset in academic librarianship. As shown by the program’s acceptance rate, demand remains high for participation in evidence synthesis training. Future programming could build on past success, such as continuing to offer synchronous virtual Institutes, training additional instructors, and expanding the asynchronous online course to include more content and summative assessments.